Report from the Killer-cell Immunoglobulin-like Receptors (KIR) component of the 17th International HLA and Immunogenetics Workshop - Misra, MK; Augusto, DG; Martin, GM; Nemat-Gorgani, N; Sauter, J; Hofmann, JA; Traherne, JA; González-Quezada, B; Gorodezky, C; Bultitude, WP; Marin, W; Vierra-Green, C; et al. (Elsevier, 2018)
The goals of the KIR component of the 17th International HLA and Immunogenetics Workshop (IHIW) were to encourage and educate researchers to begin analyzing KIR at allelic resolution, and to survey the nature and extent of KIR allelic diversity across human populations. To represent worldwide diversity, we analyzed 1269 individuals from ten populations, focusing on the most polymorphic KIR genes, which express receptors having three immunoglobulin (Ig)-like domains (KIR3DL1/S1, KIR3DL2 and KIR3DL3). We identified 13 novel alleles of KIR3DL1/S1, 13 of KIR3DL2 and 18 of KIR3DL3. Previously identified alleles, corresponding to 33 alleles of KIR3DL1/S1, 38 of KIR3DL2, and 43 of KIR3DL3, represented over 90% of the observed allele frequencies for these genes. In total we observed 37 KIR3DL1/S1 allotypes, 40 for KIR3DL2 and 44 for KIR3DL3. As KIR allotype diversity can affect NK cell function, this demonstrates potential for high functional diversity worldwide. Allelic variation further diversifies KIR haplotypes. We determined KIR3DL3 ∼ KIR3DL1/S1 ∼ KIR3DL2 haplotypes from five of the studied populations, and observed multiple population-specific haplotypes in each. This included 234 distinct haplotypes in European Americans, 191 in Ugandans, 35 in Papuans, 95 in Egyptians and 86 in Spanish populations. For another 35 populations, encompassing 642,105 individuals we focused on KIR3DL2 and identified another 375 novel alleles, with approximately half of them observed in more than one individual. The KIR allelic level data gathered from this project represents the most comprehensive summary of global KIR allelic diversity to date, and continued analysis will improve understanding of KIR allelic polymorphism in global populations. Further, the wealth of new data gathered in the course of this workshop component highlights the value of collaborative, community-based efforts in immunogenetics research, exemplified by the IHIW.